Development of Video Tutorial Learning Media Based on Biomechanical Analysis in Petanque Shooting Techniques - Epenetus Giawa; Benny Aprial. M; Liliana Puspa Sari; Alan Alfiansyah Putra Karo Karo (Journal Of Sport Education (JOPE), 2024)
This study aims to develop a tutorial video-based learning media using biomechanical analysis for petanque shooting techniques as a training support tool. The background of this research is the difficulty experienced by athletes in understanding and applying proper shooting techniques due to the limited use of instructional media during training sessions. This study employed a Research and Development (R&D) method by adapting the 4D model, which consists of define, design, development, and disseminate stages. The research instruments were assessment questionnaires administered to material experts, media experts, petanque coaches, and athletes. The data were analyzed using descriptive quantitative and qualitative techniques. The results indicate that the developed tutorial video-based learning media achieved good to very good categories in terms of material content, learning aspects, display, and programming. Athlete assessments also showed positive responses toward the use of the media in shooting training. Therefore, the tutorial video-based learning media using biomechanical analysis is feasible and effective as a supporting medium to enhance athletes’ understanding of petanque shooting techniques.